THE OVER USE OF PLANTATION LAND DUE TO BECOMING TOURISM AREA IN THE PERSPECTIVE OF SPACE PLANNING - Zubaidi ,SH (Jurnal IUS Kajian Hukum dan Keadilan, 2014)
Conversion of the land is a land use or land be put into function a form other than in accordance with the previous function parties interests involved in over the function. Over the function of plantation land into a tourism district is function a farming area to area tourism or business tourism services such as hotels, villas, resorts and tourism business. Each activity over the function of land or land use can not escape from the spatial aspects . Code space is a structure of space and pattern space. while Setup is a system of spatial planning processes , space utilization and operation of space utilization . Each activity over the function of land into a tourism area should refer to the relevant spatial area and not detrimental to the interests of others . And slowly over the function of each activity should be referred to the natural environment to maintain the balance of ecosystems and sustainable developmentKeywords : Land Function Conversion, Tourism , Spatial